Sífilis congênita no estado do Ceará: aspectos temporais e geoespaciais - Medeiros, Camila Martins de (2020)
The general objective was to analyze the temporal and spatial trend patterns of Congenital Syphilis reported in the State of Ceará between 2007 and 2016. This is an ecological study of temporal and spatial trend, conducted between the months of March 2019 and June 2020 from the compulsory notification forms of congenital syphilis accounted for in the Aggravates Notification Information System (SINAN) with all the notifications of the State between the years 2007 and 2016. An analysis of the frequency and distribution of socio-demographic data, calculation of the incidence rate of syphilis in pregnant women, incidence rate of CS in children under 1 year of age, lethality and mortality rate due to congenital syphilis were performed. For the time trend analysis performed in the Joinpoint Regress Program version 4.0.4. Descriptive maps of the region were made using the ArcGis software version 9.2. Most pregnant mothers of newborns diagnosed with congenital syphilis between the years 2007 and 2016 were young adults, brown, had low schooling (elementary school), performed prenatal care, lived in urban areas and was a housewife. As for newborns, all were diagnosed before one year of life, had a non-treponemic reagent test. During the entire study period the gestational syphilis curve was greater than that of congenital syphilis. Between 2007 and 2009 the lethality of congenital syphilis was higher in Fortaleza and metropolitan region, the incidence was higher in these same regions and Sobral was added to this list. Mortality was higher in the interior of the state. Between 2010 and 2016 the incidence and lethality of SC were higher in Fortaleza and metropolitan region and Sobral, while the mortality was higher only in cities of the interior of the state. The analysis of time trend showed that there was no statistical significance in the coefficients of CS. The coefficient of the incidence rate of CS in children under one year of age was characterized by a growing inflection from 2007 to 2009 and decreasing from 2009 to 2016. The mortality rate by congenitalsyphilis had a decreasing curve in the period 2007 to 2013 and some stability of the curve between 2013 and 2016. Even with relative stability, the goals proposed by WHO have not yet been achieved. The points where attention can be directed to the prevention of the disease: attention to the treatment of sexual partnerships, active search and greater testing during pregnancy and effective treatment during pregnancy.